Review on Biosynthesis of Tio2-Sio2 Nanocomposites Towards Photocatalytic Purpose of Wastewater Treatment: TIO2-SIO2 NANOCOMPOSITES - Abdul Ghani, Muhammad Zul Idzham; Muhd Nor, Nik Hisyamudin (Research Progress in Mechanical and Manufacturing Engineering, 2022)
This research was conducted to analyse the capability of TiO2-SiO2 nanocomposite in eliminating methylene blue dye, lead ions and contaminant in water stream such as river and sea. A review research was performed as a primary prevention to remove the issue of polluted water by treating the contaminated water generated by consumers as well as clean water that can be used. TiO2 has been extensively used as photocatalyst due to its non-toxicity, low cost and photochemical stability. Titanium Oxide nanoparticles also exhibit unique surface chemistry and morphologies. The addition of other oxides such as silicon dioxide, SiO2 was establish to enhance the thermal stability and photocatalytic activity of titanium dioxide. This is partially explained by the intimate interaction of TiO2 and SiO2, which results in new structural and physicochemical properties such as quantum-sized crystallinity, high surface area, high adsorption capacity or high acidity. Mostly TiO2-SiO2 nanocomposite are produced via physicochemical methods like chemical vapor deposition, micro emulsion, chemical precipitation, hydrothermal crystallization, and sol–gel methods. Hydrothermal method was used in synthesizing the TiO2-SiO2 nanocomposite in order to enhance the adsorption ability and photocatalytic activity in wastewater treatment. The FTIR (Fourier transform infrared spectroscopy) and Energy Dispersive and X-ray (EDX) was used to determine crystallinity and phase. The Field Emission Scanning Electron Microscope (FESEM) was used for surface morphology and analysis on the nanoparticles.